2020
DOI: 10.1111/clr.13646
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐implant tissue conditions at implants treated with Sub‐periosteal Peri‐implant Augmented Layer technique: A retrospective case series

Abstract: Objectives: To assess peri-implant tissue conditions on the short term in patients receiving the Sub-periosteal Peri-implant Augmented Layer (SPAL) technique and in patients with adequate thickness (≥2 mm) of the peri-implant buccal bone plate (PBBP) at placement. Methods: Patients where either a dehiscence defect or thin PBBP at implant placement was corrected by SPAL technique (SPAL dehiscence and SPAL thin groups, respectively) and patients presenting a residual PBBP thickness ≥2 mm at implant placement (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…Clinical observations stemming from the present case report cumulate with previous evidence from case reports 2,5 and retrospective case series 3,4 on the SPAL technique. Overall, data demonstrate that SPAL can be successfully used for peri-implant bone augmentation with a bovine-derived xenograft in a variety of clinical scenarios in terms of implant topography (i.e., anterior/posterior sextant 3 and maxillary/mandibular arch 3,4 ) as well as conditions of the buccal bone plate at the time of implant placement. In particular, clinically relevant augmentation was reported for implants with either a buccal bone dehiscence or an intact but thin buccal bone plate at placement, 4 Within implants with bone dehiscence, defect depths up to 6 mm were successfully corrected with SPAL.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Clinical observations stemming from the present case report cumulate with previous evidence from case reports 2,5 and retrospective case series 3,4 on the SPAL technique. Overall, data demonstrate that SPAL can be successfully used for peri-implant bone augmentation with a bovine-derived xenograft in a variety of clinical scenarios in terms of implant topography (i.e., anterior/posterior sextant 3 and maxillary/mandibular arch 3,4 ) as well as conditions of the buccal bone plate at the time of implant placement. In particular, clinically relevant augmentation was reported for implants with either a buccal bone dehiscence or an intact but thin buccal bone plate at placement, 4 Within implants with bone dehiscence, defect depths up to 6 mm were successfully corrected with SPAL.…”
Section: Discussionsupporting
confidence: 80%
“…Overall, data demonstrate that SPAL can be successfully used for peri-implant bone augmentation with a bovine-derived xenograft in a variety of clinical scenarios in terms of implant topography (i.e., anterior/posterior sextant 3 and maxillary/mandibular arch 3,4 ) as well as conditions of the buccal bone plate at the time of implant placement. In particular, clinically relevant augmentation was reported for implants with either a buccal bone dehiscence or an intact but thin buccal bone plate at placement, 4 Within implants with bone dehiscence, defect depths up to 6 mm were successfully corrected with SPAL. Unfortunately, although encouraging, the available data is not sufficient to either clearly delineate the local indications/contraindications of the SPAL technique or clarify which factors may influence the clinical outcomes of the procedure.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Eighteen studies were included for the analysis. NHBS and HBS were employed in 13 6,25,30,33–42 and 5 23,26,28,29,31 studies, respectively. Deproteinized bovine bone mineral and autologous bone were the most used NHBS and HBs, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Details of the included studies are reported in Table 1. Twenty‐three studies reported data on BD 6,21–42 whereas one study reported data on BF 20 . Quality assessment of the included studies is reported in Appendices 3 and 4.…”
Section: Resultsmentioning
confidence: 99%